2010
DOI: 10.1152/ajprenal.00687.2009
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory action of Wnt target gene osteopontin on mitochondrial cytochrome c release determines renal ischemic resistance

Abstract: Certain determinants of ischemic resistance in the Brown Norway rat strain have been proposed, but no studies to date have focused on the role of the Wnt pathway in the ischemic resistance mechanism. We performed a comparative genomic study in Brown Norway vs. Sprague-Dawley rats. Selective manipulations of the Wnt pathway in vivo and in vitro allowed us to study whether the action of the Wnt pathway on apoptosis through the regulation of osteopontin was critical to the maintenance of inherent ischemic resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…18 The overexpression of OPN via the hyperactivation of Wnt signaling, as detected in Brown Norway rats, is also critical for the maintenance of their inherent ischemic resistance. 20 However, OPN again stimulated the development of renal fibrosis after acute ischemic insult. 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The overexpression of OPN via the hyperactivation of Wnt signaling, as detected in Brown Norway rats, is also critical for the maintenance of their inherent ischemic resistance. 20 However, OPN again stimulated the development of renal fibrosis after acute ischemic insult. 19 …”
Section: Discussionmentioning
confidence: 99%
“…OPN reduces mitochondrial cytochrome c release and caspase 3 activity after renal I–R. 20 It has also been reported that OPN expressed in tubular epithelial cells regulates NK cell-mediated kidney I–R injury. 21 …”
mentioning
confidence: 96%
“…The data GSE9943 [13] were downloaded from the National Center for Biotechnology Information (NCBI) Genome Expression Omnibus (GEO, http://www.ncbi.nlm.nih.gov/geo/) database [14]. Totally 12 samples were available within the data, including two groups (I/R group and control group) for both Brown Norway (BN) and Sprague Dawley (SD) rats (n = 3 per group).…”
Section: Methodsmentioning
confidence: 99%
“…It was previously recognized that Brown Norway rats are particularly resistant to renal IR due to congenital increased in Wnt/β-catenin signaling relative to other species of rats (33). In another study, transfection with a vector coding for the Wnt1 ligand protected human kidney cells from apoptosis after exposure to staurosporin (7).…”
Section: Discussionmentioning
confidence: 99%